2014
DOI: 10.1111/micc.12093
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Placental Angiogenesis

Abstract: Ample interest has been evoked in using placental angiogenesis as a target for the development of diagnosis tools and potential therapeutics for pregnancy complications based on the knowledge of placental angiogenesis in normal and aberrant pregnancies. Although these goals are still far from reach, one would expect that two complementary processes should be balanced for therapeutic angiogenesis to be successful in restoring a mature and functional vascular network in the placenta in any pregnancy complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
118
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 139 publications
2
118
0
3
Order By: Relevance
“…Insulin resistance in peripheral tissues in women with GDM is exacerbated, but few studies have examined the extent of insulin resistance in placenta in this disease and the ways in which this resistance could contribute to alter the placental transport of nutrients [18,19]. Moreover, insulin, along with glucose, is involved in the regulation of angiogenesis and vasculogenesis in the fetus [20,21], where they bind to fetal endothelial cells [22]. Thus, fetal hyperinsulinemia may also contribute to the hypervascular placenta typical of GDM [23].…”
Section: Functions Of Insulin Within the Placentamentioning
confidence: 99%
“…Insulin resistance in peripheral tissues in women with GDM is exacerbated, but few studies have examined the extent of insulin resistance in placenta in this disease and the ways in which this resistance could contribute to alter the placental transport of nutrients [18,19]. Moreover, insulin, along with glucose, is involved in the regulation of angiogenesis and vasculogenesis in the fetus [20,21], where they bind to fetal endothelial cells [22]. Thus, fetal hyperinsulinemia may also contribute to the hypervascular placenta typical of GDM [23].…”
Section: Functions Of Insulin Within the Placentamentioning
confidence: 99%
“…This process is necessary for the development of the fetal vascular system in the placental villous tree and development of an adequate uteroplacental circulation. 5 Soluble fms-like tyrosine kinase (sFlt-1), an antiangiogenic factor secreted by endothelial cells, can block the effect of PlGF. 4 Previous studies showed that lower PlGF levels can disrupt the normal process of neoangiogenesis, whereas higher sFlt-1 levels during pregnancy can lead to systemic endothelial dysfunction.…”
mentioning
confidence: 99%
“…31,32 Our results evidenced that TiO 2 NP treatment resulted in placental vascular collapse and it impaired the formation of an intricate network of fetal vessels. Similar to our results, Yamashita et al found that spiral artery canals failed to form and blood flow was significantly reduced in the fetal vascular sinuses of 70 nm TiO 2 NP-treated mice.…”
mentioning
confidence: 83%
“…32 Furthermore, Stapleton et al reported that thrombosis was observed in the pulmonary vascular system of TiO 2 NP-treated mice, which could be induced by the blocking of blood vessels with TiO 2 particles. 33 In addition, uNK cells are short-lived, terminally differentiated and the most abundant lymphocyte in the uterus, and play a vital role in vascularization, spiral arteriole modification and placentation.…”
mentioning
confidence: 99%